Pengaruh Peran Orang Tua dan Aksesibilitas Buah dan Sayuran terhadap Rendahnya Konsumsi Buah dan Sayur pada Anak Pra Sekolah di Kota Bima Nusa Tenggara Barat - Rostinah Rostinah; Nelly Nelly (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
Early childhood is critical to the development of lifelong food habits. Given the high proportion of children with inadequate fruit and vegetable consumption, identification of modifiable factors associated with higher consumption may be useful in developing interventions to address this public health issue. The aim of the present study was to investigate factors that affect fruit and vegetable consumption in a sample of Mpunda districts preschool children. Methods using A cross-sectional telephone survey and questioner was conducted with 60 parents of 3 to 5 year-old children. Children’s fruit and vegetable consumption was measured using a valid and reliable subscale from the Children’s Dietary Questionnaire. Associations were investigated between children’s fruit and vegetable intake and characteristics of the home food environment including parental role-modeling, parental providing behaviour, fruit and vegetable availability, fruit and vegetable accessibility, pressure to eat, education and knowlwdge, family mealtime practices. Characteristics of the home food environment that showed evidence of an association with children’s fruit and vegetable consumption in simple regression models were entered into a backwards stepwise multiple regression analysis. The multiple regression analysis found positive associations between children’s fruit and vegetable consumption and parental fruit and vegetable intake (p = 0.004), and accessibility (p = 0.002).